مدنی زندگی میں'' تصورامت ''کا تدریجی ارتقاء: وائل حلاق کے افکارکا خصوصی مطالعہ (Al-Qamar, 2024)
Today, the primary issue facing any modern culture is moral decay. The harm that results from this impacts each person as well as society. Given the significance of moral philosophy, many academics in the West are attempting to resolve moral issues. Among them are the well-known names of Weber, Kelsen, Schmidt, Marx, Foucault, Gramsci, and Cartwright David. The project of Professor Wael Hallaq is very crucial in this regard. Among western scholars, there is a little difference in the understanding of each term based on knowledge; in the same way, there is a difference in the introduction and formation of the philosophy of ethics. Despite the disagreement with Wael Halaq on this basis, the dialogue can be carried forward in the formation of a "modern project" for the reform of society. Its possible situation is the reformation of the "Concept of Ummah" along with the reformation of other theories of Hallaq. In the teachings given by Allah, there is a universal concept of the unity of Ummah and religion. Despite this, according to the will of God Almighty, the difference in human thoughts and actions has been the reason for the formation of "new nations.". In the seventh century (610 A.D.), Allah Almighty organized the reformation of humanity away from the path of guidance by sending the Messenger of Mercy (peace be upon him). The Holy Prophet (peace and blessings of Allah be upon him) provided equal opportunities for social construction to other nations with the establishment of Islamic Sharia supremacy for the welfare of humanity. Even today, the Muslim Ummah should be strong and united and move forward to fulfill this duty and the Sunnah of the Prophet (peace and blessings of Allah be upon him). Moral reform is one of the basic teachings of Islam. According to the Holy Quran, the Holy Prophet (peace and blessings of Allah be upon him) was awarded the highest status of morals. Thus, it is appropriate to welcome any person or country that aspires to restructure contemporary states under the primacy of Islamic Sharia and is prepared to collaborate with Muslims in resolving issues. The article under discussion describes the development of the "Islamic Concept of Ummah" within the framework of the many ideas of Wael Hallaq. In this context, it presents suggestions for the solution of contemporary global problems as a philosophy of ethics in the form of "Unity of Nation".
Keywords: Ethics; Ummah; Unity of the nation; Modern Project; Sunnah of the Prophet (peace be upon him); Welfare of humanity